Behavior change interventions for dangerous driving behavior in low- and middle-income countries: a systematic review of interventions and outcome measurement instruments - Fanai, Saen; Okyere, Eunice; Marfoh, Kissinger (Frontiers in Public Health, 2025)
ObjectiveThis systematic review aims to assess Behavior Change Interventions (BCIs) targeting dangerous driving behaviors (DDBs) in low- and middle-income countries (LMICs), evaluate their effectiveness, and explore the outcome measurement instruments employed in these contexts.MethodA comprehensive search was performed across key databases such as Scopus, PubMed, CINAHL, Medline, ProQuest, Cochrane Library, and Research4life, focusing on studies published post-2015 on BCIs for DDB using randomized controlled trials (RCTs), quasi-experiments and mixed method designs. Data extraction centres on the types of intervention, theoretical frameworks, outcome measurement, and intervention effectiveness. The findings were analyzed through a narrative synthesis approach.ResultsFifteen studies were analyzed in this review, which examined BCIs aimed at enhancing driver behavior. Some interventions included public awareness campaigns, peer mentorship programs, driving courses for skill enhancement, and in-vehicle monitoring systems for safety measures. The study results revealed that widely employed behavior change theories such as the Theory of Planned Behavior (TPB), along with Social Cognitive Theory (SCT) and the Health Belief Model (HBM), were prevalent in these interventions. Surveys like the Driver Behavior Questionnaire (DBQ) and assessments of road safety knowledge were frequently used to measure behavioral changes among participants. Objective criteria included the use of GPS tracking devices, as well as the examination of insurance claims and traffic violation reports to evaluate the interventions’ effectiveness. The study focused on methods like peer influence implementation and fear-based communication strategies paired with personalized feedback, which were identified as successful approaches in the review report. However, it emphasized a lack of uniformity in utilizing validated tools for outcome measurement across various socioeconomic contexts, particularly in LMICs.ConclusionBehavioral interventions informed by theories have demonstrated effectiveness in improving driving behaviors; nonetheless, recognized and validated measures for assessing results in lower—and middle-income settings remain unclear. In the future, research efforts should prioritize developing assessment tools that resonate with cultures and conducting studies to evaluate enduring changes in behavior. This systematic review may guide policymakers, and public health experts engaged in developing road safety programs.Systematic review registrationwww.crd.york.ac.uk/prospero, identifier 578081.